2003
DOI: 10.1002/zaac.200200424
|View full text |Cite
|
Sign up to set email alerts
|

Single Crystal X‐ray Diffraction Study of CsHSi2O5

Abstract: Hydrothermally synthesized CsHSi 2 O 5 was studied by single-crystal X-ray diffraction. The compound is orthorhombic (space group Pnma). Unit cell parameters are a ϭ 4.9758(3), b ϭ 8.8089 (6), c ϭ 12.9295(9) Å with four formula units per cell. The structure was solved by direct methods and refined to a residual R 1 ϭ 0.025 for 621 independent observed reflections with I > 2σ(I) and 41 parameters. Residual electron densities were used to locate positions of the H atoms. They are part of silanol groups and show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 18 publications
(10 reference statements)
1
1
0
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16][17] However, such linear silicates that include only a caesium (Cs) cation have been barely reported. In this study, we report a low-dimensional caesium silicate (abbreviated as LDS-1), 18 which is a very similar polymorph of CsHSi 2 O 5 reported by Do¨rsam et al 19 LDS-1 was obtained under solidstate reaction conditions. The crystal structure of CsHSi 2 O 5 comprises alternating alignments of zigzagged silica frameworks, and the Cs cations are stabilized in the elliptical spaces formed by the chain-like framework.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15][16][17] However, such linear silicates that include only a caesium (Cs) cation have been barely reported. In this study, we report a low-dimensional caesium silicate (abbreviated as LDS-1), 18 which is a very similar polymorph of CsHSi 2 O 5 reported by Do¨rsam et al 19 LDS-1 was obtained under solidstate reaction conditions. The crystal structure of CsHSi 2 O 5 comprises alternating alignments of zigzagged silica frameworks, and the Cs cations are stabilized in the elliptical spaces formed by the chain-like framework.…”
Section: Introductionsupporting
confidence: 67%
“…Structural distortion of the framework depended on the charge balance among the open framework, Cs + ions, and protons. Do¨rsam et al 19 also reported this unusually short bond length due to tetrahedra distortion for CsHSi 2 O 5 . The nearest atomic distance between adjacent silanol groups was short, that is, l(O-O) was only ca.…”
Section: X-ray Structure Analysismentioning
confidence: 83%